Rule Britannia : politics in British Montserrat - Fergus, Howard A. (UWI. University Centre PlymouthMS, 1985)
Gives a brief history of the constitution in Montserrat. Comments on the electoral behaviour in this British dependency from 1952 to the present. Sketches are given of major male and female personalities in Montserratian politics. Examines the issue of decolonization commenting on the attitudes of the politicians towards independence.